2011
DOI: 10.1073/pnas.1105151108
|View full text |Cite
|
Sign up to set email alerts
|

Targeted translational regulation using the PUF protein family scaffold

Abstract: Regulatory complexes formed on mRNAs control translation, stability, and localization. These complexes possess two activities: one that binds RNA and another-the effector-that elicits a biological function. The Pumilio and FBF (PUF) protein family of RNA binding proteins provides a versatile scaffold to design and select proteins with new specificities. Here, the PUF scaffold is used to target translational activation and repression of specific mRNAs, and to induce specific poly(A) addition and removal. To do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
65
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 51 publications
1
65
0
1
Order By: Relevance
“…By linking a modified PUF to an effector domain, regulation can be targeted to specific mRNAs (39)(40)(41). The plasticity of interactions reported here raises considerations for such studies: Flexibility may cause off-target effects.…”
Section: Discussionmentioning
confidence: 99%
“…By linking a modified PUF to an effector domain, regulation can be targeted to specific mRNAs (39)(40)(41). The plasticity of interactions reported here raises considerations for such studies: Flexibility may cause off-target effects.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that our individual PPR modules can be combined within the engineered cPPR proteins with the capacity to modify their binding specificities to single-nucleotide level, providing further evidence of their modularity. We thus demonstrate that they might be engineered to target and manipulate RNAs of interest, as has been the case for PUFs 7,26,37,[39][40][41][42][43][44][45][46] . Here we focused on engineered proteins with eight PPRs.…”
Section: Discussionmentioning
confidence: 99%
“…Reporter RNA Plasmids-The pLG-MS2 (firefly luciferase), pLG-MS2ϩA39 (polyadenylated firefly luciferase), pSP65-ren (Renilla luciferase), pLGMS2-luc (RNA with three MS2-binding sites), pLGMS2ϩA39-luc (RNA with three MS2-binding sites and a poly(A) 39 tail), pLG:FBE-ACAmut (RNA that lacked MS2 binding sites), and pLG:FBE-ACAmutϩA39 (RNA with a poly(A) 39 tail that lacked MS2 binding sites) plasmids have been described (41)(42)(43)(44).…”
Section: Methodsmentioning
confidence: 99%
“…Luciferase Assays and Western Blotting-Dual-Luciferase assays (Promega) and Western blotting were performed as described (35,43). Student's two-tailed t tests were used to calculate all p values.…”
Section: Methodsmentioning
confidence: 99%